Clinical implication of Keap1 and phosphorylated Nrf2 expression in hepatocellular carcinoma. (20th September 2016) - Chen, Jiang; Yu, Yaojun; Ji, Tong; Ma, Rui; Chen, Mingming; Li, Gaofeng; Li, Feibo; Ding, Qiong; Kang, Qingsong; Huang, Diyu; Liang, Xiao; Lin, Hui; et al.
Abstract: In this paper, variation tendency of phosphorylated Nrf2, as the activated form of native Nrf2, was studied in 107 primary hepatocellular carcinoma (HCC) specimens treated by curative hepatectomy. Moreover, the coexpression of oxidative stress markers Keap1 and pNrf2, and their association with pathological features were also evaluated based on those specimens. The results showed that preserved cytoplasmic Keap1 expression of cancer cells was observed in 59 HCCs, while reduced Keap1 expression was determined in remaining 48 ones. With regarding to nuclear pNrf2 expression, 75 HCCs were defined as high and the other 32 ones as low. There was a significant association between Keap1 and pNrf2 expression in HCCs. Higher pNrf2 expression was observed, at a more substantial proportion, in those specimens with reduced Keap1 expression, compared to those with preserved Keap1 expression. The subset with higher pNrf2 and reduced Keap1 expression was defined as pNrf2 + Keap1 − . According to the analysis of prognosis, this subset was significantly associated with poor 5‐year overall survival and worse disease‐free survival in HCCs, indicating that pNrf2 and Keap1 were two‐functional biomolecules, not only the oxidative stress markers but also biomarkers for prognosis of HCCs. Abstract : Oxidative stress has a crucial clinical significance on patients in a variety of tumors. However, there has been no comprehensive analysis of the role and clinical significance of oxidative stress markers Keap1 and pNrf2 expression in hepatocellular carcinoma (HCC). We found that reduced expression of cytoplasmic Keap1 and positive expression of nuclear pNrf2 of cancer cells may be associated with poor clinical outcome and worse prognosis.